Natural products for managing metabolic syndrome: a scoping review - Abdulghani, Mohammed Faris; Al-Fayyadh, Sadeq (Frontiers in Pharmacology, 2024)
Introduction: Metabolic syndrome comprises a collection of metabolic disorders stemming from factors like genetic predisposition, inadequate nutrition, stress, decreased physical activity, aging, and ethnicity. Although traditional pharmaceutical treatments exist for metabolic syndrome, their limited popularity is attributed to high costs and adverse effects. Consequently, natural products with fewer side effects have been explored for managing this condition. This literature review aims to explore the role of natural products including herbs, botanicals, vitamins, minerals, probiotics, and dietary supplements in managing metabolic syndrome. Methods: This scoping review was conducted in five steps, involving the formulation of a research question, the retrieval and extraction of relevant studies, the selection of pertinent studies, the organization of information into tables, and the reporting of results. Data was collected from various databases including Embase, Science Direct, PubMed, Google Scholar, Scopus, and Web of Science, with a focus on studies published from 2010 to the present, available in English and with full-text accessibility. Results: We identified 1259 articles, screened their titles, abstracts, and full texts, ultimately incorporating 169 pertinent articles into this review (comprising 90 review articles, 32 trial articles, 6 in vitro articles, 38 in vivo articles, 1 experimental article and 2 observational articles). The study's outcomes revealed that natural products, encompassing plants and their derivatives, vitamins and supplements, as well as probiotics, can exert a beneficial influence on metabolic syndrome by regulating blood sugar, blood pressure, lipid profiles, obesity, and abnormal cholesterol and triglyceride levels. Conclusion: The current study underscores the significance of natural products in addressing metabolic syndrome. Consequently, it is advisable to conduct further extensive research to assess the efficacy of these products, potentially integrating them into treatment regimens for individuals with metabolic syndrome.